Rabbits - Barrett, Norman S.; Burns, Rhoda; Burns, Robert; Henrie, Marc (New York : F. Watts, 1990)
Examines various rabbits around the world, describing their social, reproductive, and feeding habits and providing tips for their proper care.
Includes index.
4.1
3-5.
3-6
Keywords: Rabbits -- Juvenile literature; Rabbits; Rabbits